PrevAleNce and Associated factors of inappropriaTe dosing of direct Oral anticoaguLants In pAtients with Atrial Fibrillation: the ANATOLIA-AF Study - Kocabaş, Umut; Ergin, Isil; Yavuz, Veysel; Murat, Selda; Özdemir, Ibrahim; Genç, Ömer; Okar, Sefa (Springer, 2024)
Purpose: Inappropriate dosing of direct oral anticoagulants is associated with an increased risk of stroke, systemic embolism, major bleeding, cardiovascular hospitalization, and death in patients with atrial fibrillation. The main goal of the study was to determine the prevalence and associated factors of inappropriate dosing of direct oral anticoagulants in real-life settings. Methods: This study was a multicenter, cross-sectional, observational study that included 2004 patients with atrial fibrillation. The study population was recruited from 41 cardiology outpatient clinics between January and May 2021. The main criteria for inappropriate direct oral anticoagulant dosing were defined according to the recommendations of the European Heart Rhythm Association. Results: The median age of the study population was 72 years and 58% were women. Nine-hundred and eighty-seven patients were prescribed rivaroxaban, 658 apixaban, 239 edoxaban, and 120 dabigatran. A total of 498 patients (24.9%) did not receive the appropriate dose of direct oral anticoagulants. In a logistic regression model, advanced age, presence of chronic kidney disease and permanent atrial fibrillation, prescription of reduced doses of direct oral anticoagulants or edoxaban treatment, concomitant use of amiodarone treatment, and non-use of statin treatment were significantly associated with potentially inappropriate dosing of direct oral anticoagulants. Conclusion: The study demonstrated that the prevalence of inappropriate direct oral anticoagulant dosing according to the European Heart Rhythm Association recommendations was 24.9% in patients with atrial fibrillation. Several demographic and clinical factors were associated with the inappropriate prescription of direct oral anticoagulants. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2022.
Keywords: Atrial fibrillation; Direct oral anticoagulants; Inappropriate dosing; Stroke; Systemic embolism